Individual investor investment alternatives assessment criteria modelling - Kiyak, Deimena (Buhalterinės apskaitos teorija ir praktika, 2014)
Private investment is one of the most important people financial components. Basically, it is an investment activity undertaken by individuals. In most cases investment efforts are intended to ensure the financial security later in life. The choice of them is relatively wide. However, for individual investors information about this receipt flow frequent is limited or poorly accessible. Therefore individual investors potential types of investment choices, their benefits and disadvantages of summation research in this area is valuable, relevant and new, both in theoretical and practical terms. Objective of the study - conclude individual investors potential investment alternatives selection model under the most relevant criteria. For an individual investor to understand the possible role of investment and management capabilities article summarizes the works of scientists presented the concept of investment. Individual investor's investment - is the active use of money, during which the money earns money and work for people and the partially guarantees additional revenue, provide permanent capital increase to satisfy the personal needs, implementing personal financial goals. For individual investor is most relevant investment funds classify according to investment properties, investor type and by period of investment and risk levels. In order to evaluate the investment options preferred by an individual investor was identified seven individual investors potential investment alternatives evaluation criteria: low risk of losing money; a high return; the initial amount of capital; lack of knowledge; access to information; short payback period; lack of need for continuous investment. In Article individual investor's investment options structured, provided essential types of investments advantages and disadvantages, also investments divided into two main groups. 1. Investment alternatives that do not require a large initial capital or nor the additional knowledge, and with little risk of losing money, the long payback period, adequate information dissemination about them, but with little return (deposits, government saving measures, gold). 2. Investment options on which information is available in difficult, often require additional knowledge, a bigger risk of losing money, but a short payback period (stocks, real estate, art values).
Keywords: investments; types of investment; alternatives of individual investor investment